ASIATIC ACID INFLUENCES GLUCOSE HOMEOSTASIS IN P. BERGHEI MURINE MALARIA INFECTED SPRAGUE-DAWLEY RATS - Mavondo, Greanious Alfred; Mkhwanazi, Blessing Nkazimulo; Mabandla, Musa Vuyisile; Musabayane, Cephas Tagumirwa (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Glucose homeostasis derangement is a common pathophysiology of malaria whose aetiology is still controversial. The Plasmodium parasite, immunological and inflammatory responses, as well as chemotherapeutics currently used cause hypoglycaemia in malaria. Anti-parasitic and anti-disease drugs are required to combat malaria while ameliorating the pathophysiology of the infection. Asiatic acid has anti-hyperglycaemic, antioxidant, pro-oxidant properties useful in glucose homeostasis but its influence in malaria is yet to be reported. Here we present findings on the influence of asiatic acid on glucose metabolism in vivo using P. berghei-infected Sprague Dawley rats. Materials and Methods: Acute as well as sub-chronic studies were carried out in vivo where physicochemical properties and glucose homeostasis were monitored after administration of asiatic acid (10mg/kg) in both non-infected and infected animals. Glucose metabolism associated biochemical changes in malaria were also investigated. Results: In acute studies, asiatic acid improved oral glucose response while in the sub-chronic state it maintained food and water intake and suppressed parasitaemia. Normoglycaemic control was maintained in infected animals through insulin suppression and increasing glucagon secretion, in both acute and chronic studies. Asiatic acid administration curtailed lactate concentration towards normal. Conclusion: Per oral post-infection asiatic acid administration preserved drinking and eating habits, inhibited sickness behaviour while suppressing parasitaemia. Reciprocal relationship between insulin and glucagon concentrations was maintained influencing glucose homeostasis positively and inhibition of hyperlactaemia in malaria.